Creating character : Theories of nature and nurture in Victorian sensation fiction - Ifill, Helena (Book collections on Project MUSE., 2018)
This book explores the ways in which the two leading sensation authors of the 1860s, Mary Elizabeth Braddon and Wilkie Collins, engaged with nineteenth-century ideas about personality formation and the extent to which it can be influenced either by the subject or by others. Innovative readings of seven sensation novels explore how they employ and challenge Victorian theories of heredity, degeneration, inherent constitution, education, upbringing and social circumstance. Far from presenting a reductive depiction of 'nature' versus 'nurture', Braddon and Collins show the creation of character to be a complex interplay of internal and external factors. Drawing on material ranging from medical textbooks, to sociological treatises, to popular periodicals, Creating character shows how sensation authors situated themselves at the intersections of established and developing, conservative and radical, learned and sensationalist thought about how identity could be made and modified.